Cutting-edge approaches to B-cell depletion in autoimmune diseases - Robinson, William H.; Fiorentino, David; Chung, Lorinda; Moreland, Larry W.; Deodhar, Malavika; Harler, Mary Beth; Saulsbery, Carrie; Kunder, Rebecca (Frontiers in Immunology, 2024)
This article provides an in-depth examination of current and emerging modalities of B-cell depletion therapy (BCDT), with a focus on effector-function-enhanced monoclonal antibodies, chimeric antigen receptor T-cell treatment, and T-cell engagers. Leveraging the demonstrated efficacy and safety of BCDT modalities in oncology, these approaches are now being applied for the treatment of autoimmune conditions, such as rheumatoid arthritis and systemic lupus erythematosus. We briefly discuss the timeline of BCDT innovations, review the molecule design and mechanism of action of each BCDT modality, and discuss their potential advantages and limitations with respect to efficacy and safety. We also provide an overview of the current knowledge of BCDTs for treating autoimmune disease, including a comprehensive listing of registered clinical trials testing BCDT modalities in autoimmune disease.